Perbandingan Kinerja Routing Multi-Copy dengan Manajemen Buffer Last In First Out pada Delay Tolerant Network - Benedict Abednego Hasibuan; Nurul Hidayat (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Some areas do not have adequate internet connectivity due to large delays and high loss rates on the network. These problems can be solved by applying the concept of Delay Tolerant Network (DTN). DTN has advantages in overcoming networks with low connectivity, large delays and high loss rates. In DTN network there is Multi-Copy routing which can increase data transmission speed and reduce delay, but this routing model requires more network resources such as buffer size. Optimizing the buffer space can be overcome by adding buffer management and Packet Priority, while the Stationary Relay Node can be used to increase the possibility of sending messages successfully. The research applies the Multi-Copy routing protocol by adding buffer management Last In First Out, Stationary Relay Node and Packet Priority simulating it with ONE simulator. Tests were carried out on Spray and Wait, Epidemic and MaxProp routing using three test parameters, namely Overhead Ratio, Delivery Probability and Latency Average. The test results show that the Spray and Wait routing performance is more optimal than other routing protocols with an Overhead Ratio value of 5.1298 with the Stationary Relay and Delivery Probability of 94.93% in a 5MB buffer with Stationary Relay. Meanwhile, the lowest Latency Average value is in MaxProp routing of 993.8513 seconds without the addition of a Stationary Relay Node.